Practical JBoss Seam projects - Farley, Jim.; SpringerLink (Online service) (Berkeley, CA : Springer, 2007)
Provides information on developing and running Web applications with JBoss Seam.
Includes index.
User level: Intermediate-Advanced.
Keywords: JBoss; Web servers -- Management; Java (Computer program language); Application software -- Development; Client/server computing